2004
DOI: 10.1182/blood-2003-07-2582
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa9 influences the phenotype but not the incidence of Mll-AF9 fusion gene leukemia

Abstract: Identification of the targets of mixed lineage leukemia (MLL) fusion genes will assist in understanding the biology of MLL fusion gene leukemias and in development of better therapies. Numerous studies have implicated HOXA9 as one of the possible targets of MLL fusion proteins. To determine if HOXA9 was required for leukemia development by MLL fusion genes, we compared the effects of the Mll-AF9 knock-in mutation in mice in the presence or absence of Hoxa9. Both groups of mice showed myeloid expansion at 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 26 publications
10
126
1
Order By: Relevance
“…On one hand, Hox genes are orderly activated in normal hematopoietic progenitors and preleukemia cells (Kumar et al, 2004;Yan et al, 2006a), in accordance with the colinear expression pattern that is observed during embryonic development. One the other hand, the expression patterns of paralogous Hox genes seen in embryonic development are not obvious in hematopoietic progenitors and cell lines, but rather whole clusters (or large regions of a cluster) are turned on or off in a lineage-specific manner.…”
Section: Expression Patterns Of Hox Genes In Hematopoietic Cellssupporting
confidence: 68%
See 2 more Smart Citations
“…On one hand, Hox genes are orderly activated in normal hematopoietic progenitors and preleukemia cells (Kumar et al, 2004;Yan et al, 2006a), in accordance with the colinear expression pattern that is observed during embryonic development. One the other hand, the expression patterns of paralogous Hox genes seen in embryonic development are not obvious in hematopoietic progenitors and cell lines, but rather whole clusters (or large regions of a cluster) are turned on or off in a lineage-specific manner.…”
Section: Expression Patterns Of Hox Genes In Hematopoietic Cellssupporting
confidence: 68%
“…In accordance with chromatin domain, 5 0 HoxA cluster genes are sequentially activated in MLL-AF9-transduced hematopoietic cells. All 5 0 HoxA cluster genes (Hoxa5-13) are hyperexpressed in MLL-AF9 leukemia cells, whereas only Hoxa5-9 genes are activated in MLL-AF9 preleukemic cells (Kumar et al, 2004;Yokoyama et al, 2005;Yan et al, 2006a). These data suggest that 5 0 HoxA cluster genes are divided into at least two chromatin domains, whereas Hoxa5-9 genes are transcriptionally delimited from Hoxa10-13 by a speculated insulator.…”
Section: Establishment Of Hox Expression Domainmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, MLL-ENL immortalization of myeloid progenitor cells could be substituted for by overexpression of HoxA9 and Meis1 (Zeisig et al, 2004), and was dependent on the activity of the oncoprotein c-Myc (Schreiner et al, 2001), a downstream effector of Hoxb4 that is sufficient to induce HSC self-renewal (Satoh et al, 2004). By contrast, analogous studies in a germline mouse model of Mll-AF9-mediated leukemogenesis suggest that Hoxa9 is not necessary for leukemia but does influence the phenotype of the leukemia (Kumar et al, 2004). Gene expression profiling of Mll-AF9-expressing BM cells revealed overexpression of the Hoxa cluster genes, Hoxa5 to Hoxa9, which the authors propose represents the Mll-AF9-triggered 'Hox code' that defines this oncogene.…”
Section: Mll Fusion Genesmentioning
confidence: 99%
“…Further, HOX A9 was found to be indispensable for ALL-1-dependent leukaemogenesis in vivo. Applying a complementary approach, Kumar et al (2004) bred mice to obtain animals transgenic for MLL-AF9 and null for HOX A9 and examined leukaemia development. Surprisingly, the absence of HOX A9 did not affect the incidence and latency of leukaemia, although the malignant cells displayed a more immature myeloid phenotype.…”
Section: Gene Expression Profiles Of All-1 Leukaemiasmentioning
confidence: 99%